Regulating Assembly of Porous Electrode Catalyst Layers - Srivastav, Harsh; Radke, Clayton J.; Weber, Adam Z. (Meeting abstracts (Electrochemical Society), 2024)
Polymer-electrolyte fuel cells (PEFCs) demonstrate remarkable potential in replacing non-renewable energy resources in paving the way for a sustainable future. PEFCs have fairly high efficiencies and energy densities, making them feasible for applications such as transportation and energy storage. The most expensive units of the PEFCs are the catalyst layers, traditionally composed of platinum interspersed on a carbon support with a perfluorosulfonic acid (PFSA) which stabilizes the ink dispersions as well acts as a binder for the dried catalyst layers. Despite the great importance of optimizing the composition of the catalyst layer to improve the practicality of PEFCs, predicting the performance of the final structure of the fuel cell remains a challenge. In this talk, we outline an approach to predict key properties of the catalyst layers such as the porosity and particle sizes that compose it through mathematical modeling of the ink properties. We discuss a kinetics-based algorithm based on interacting particles that simultaneously solves for the size distributions of the particles and the pH of the ink, a parameter that can be used for verification. The results of the aggregation formulation will be fed into calculations to determine fundamental properties of the catalyst layer, such as porosity through a void fraction calculation. To verify the accuracy of this approach, we will compare against experimental data for varying concentrations and solvents. The insights gained from these considerations will enable efficient design of future catalyst layers.